2009
DOI: 10.1097/mnm.0b013e32832ee93b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular PET and PET/CT imaging of tumour cell proliferation using F-18 fluoro-L-thymidine: a comprehensive evaluation

Abstract: Positron emission tomography (PET) using F-18 fluoro-3'-deoxy-3-L-fluorothymidine (FLT) offers noninvasive assessment of cell proliferation in vivo. The most important application refers to the evaluation of tumour proliferative activity, representing a key feature of malignancy. Most data to date suggest that FLT is not a suitable biomarker for staging of cancers. This is because of the rather low fraction of tumour cells that undergo replication at a given time with subsequently relatively low tumour FLT upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 62 publications
0
71
0
1
Order By: Relevance
“…The tumor uptake of [ 18 [24,25] and others [26,27] in vitro and in patients. These observations, considered as a "flare" phenomenon, were to be taken into account when interpreting […”
Section: Discussionmentioning
confidence: 99%
“…The tumor uptake of [ 18 [24,25] and others [26,27] in vitro and in patients. These observations, considered as a "flare" phenomenon, were to be taken into account when interpreting […”
Section: Discussionmentioning
confidence: 99%
“…18 F-fluorothymidine ( 18 F-FLT) has been proposed to directly assess DNA synthesis to estimate tumor cell proliferation and has been proposed for therapy monitoring, based on the concept that change in DNA synthesis should be the most direct index of therapeutic effects on tumor proliferation (59). A direct correlation between 18 F-FLT uptake and Ki67 expression in tumor cells has been documented (56), leading to the use of this tracer in many tumor types as a surrogate for aggressiveness and an early marker of response (39,56,(107)(108)(109)(110)(111). Obviously, tumor size is an important prognostic indicator, and tumor volume determined by 18 F-FLT was assumed to be a better predictor of overall survival than the intensity of uptake (112).…”
Section: F-fluorothymidinementioning
confidence: 99%
“…Initial efforts focused on synthesizing analogs of thymidine, because thymidine is used by proliferating cells for DNA synthesis during the S-phase of the cell cycle but, unlike other nucleosides, is not incorporated into RNA. 60 The gold standard for assessing proliferation in vitro has long been 3 H-thymidine incorporation. 17 More recently, studies using 11 C-thymidine and PET demonstrated promise in assessing response to therapy; however, the short half-life of 11 C and its rapid metabolism to thymine and other metabolites made 11 Cthymidine impractical for routine clinical use outside of academic centers.…”
Section: Imaging Proliferationmentioning
confidence: 99%
“…In addition, FLT demonstrates significant interfering physiologic activity in bone marrow and liver, and proliferating lymphocytes in reactive lymph nodes still have the potential to yield false-positive findings. 60,66 Thus, it is unlikely that FLT will have a dominant role in the initial diagnosis and staging of most cancers. Conversely, there is a general consensus that FLT-PET can be a valuable method for monitoring tumor response to treatment, especially as an early measure of response.…”
Section: Imaging Proliferationmentioning
confidence: 99%
See 1 more Smart Citation